Facilitating Basic Arabic Learning Using the Duolingo Arabic App at RA al-Husna Krejingan Kraksaan - Yayah Robiatul Adawiyah; Zahrotul Nur Aini; Azizah Lailatuzzahrah; Siti Maimuna; Nadia Zulfa Hidayah (CENDEKIA: Jurnal Pengabdian Masyarakat, 2025)
Advancements in information technology over the past two decades have brought significant changes across various fields, including foreign language education. One of the rapidly developing innovations is the emergence of application-based learning platforms, which enable users to study languages in a flexible, interactive, and autonomous manner. In the context of Arabic language learning, digital applications offer a practical alternative solution for learners from diverse backgrounds, especially those with limited access to formal educational institutions. The partner in this community service activity is Raudlatul Athfal (RA) Al-Husna, which faces challenges in teaching basic Arabic, particularly due to the lack of interactive and engaging learning media for early childhood students. Based on initial observations, the learning process remains conventional, resulting in suboptimal interest and understanding of Arabic vocabulary among children. This service activity involves mentoring and training on the use of the Duolingo Arabic application for teachers and students at RA Al-Husna as an alternative digital learning medium that is both engaging and accessible. The proposed solutions include technical training on the application's usage, direct assistance during learning sessions, and the development of a user guide tailored to the students’ characteristics. The results show an increase in students’ enthusiasm and teachers’ effectiveness in utilizing technology as a learning tool. This service demonstrates that digital application utilization can serve as an innovative solution in enhancing basic Arabic language skills in early childhood education institutions.